Systematic Literature Review Using Big Data Analysis: Cyberbullying dan Forgiveness pada Remaja - Jannah, Dwi Susi Miftakhul; Setiyowati, Ninik (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2024)
Teenagers are the age group that accesses social media the most for several purposes such as communicating, seeking information, seeking entertainment, etc. The large use of social media among teenagers can provide opportunities for teenagers to become victims of cyberbullying. Cyberbullying can have negative impact on the physical and mental health of its victims and therefore protective factors are needed from the negative impacts that arise. In this case, researchers want to know the relationship between cyberbullying and forgiveness in teenagers. This research uses a systematic literature review method by searching for articles with the help of Publish or Perish software based on keywords determined by the researcher. Based on these keywords, researchers found more than 600 articles that were published in 2018-2023 and then 16 articles that were closely related to this research were used. The research results show that cyberbullying is related to forgiveness because based on several studies it was found that forgiveness is a protective factor from the negative impact of cyberbullying. Adolescents who practice forgiveness will preventing victims from taking revenge against perpetrators and preventing victims from becoming perpetrators of cyberbullying, have fewer negative influences, have higher life satisfaction, mental health, happiness, psychological well-being and subjective well-being, and process anger appropriately. The implications of this research refer to the importance of the environment around teenagers such as parents, teachers, etc. to suppress risk factors for cyberbullying and an understanding of the importance of forgiveness also needs to be instilled in teenagers when cyberbullying occurs to them so that it can reduce the negative effects that can arise.